Transfer of oxytetracycline from ovine spiked milk to whey and cheese. (July 2017) - Cabizza, Roberto; Rubattu, Nicolino; Salis, Severyn; Pes, Massimo; Comunian, Roberta; Paba, Antonio; Addis, Margherita; Testa, M. Cecilia; Urgeghe, P. Paolo
Abstract: Cheese-making trials with ovine milk spiked with oxytetracycline (OTC) at maximum residue limit (MRL) level were performed to study the OTC distribution between whey and cheese, and assess its effect in cheese-making process and cheese composition. An in-house validated method, based on liquid chromatography-tandem mass spectrometry, was adopted to detect OTC in milk, whey and cheeses. The MRL OTC spike induced a delay in the pH lowering causing a higher moisture content in 1-day OTC cheese compared with the control cheese. No effects of OTC were observed on the mass balance of the process, on the recovery of fat and protein and, in general, on physico-chemical parameters and gross composition of obtained cheeses. OTC was mainly recovered in the 1-day cheeses (61 ± 5%). Despite a 17 ± 8% OTC reduction observed during cheese ripening, probably due to partial degradation, remaining residues were not negligible and could contribute to reach the acceptable daily intake.